OPTIMALISASI PENDIDIKAN ANAK USIA DINI BERDASARKAN PEMBELAJARAN YANG BERBASIS PERKEMBANGAN OTAK - Siti Raf'ah Azizah; Nopika Dwi Arofah; Agus Sumitra (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
Brain-based learning is a comprehensive approach to instruction based on how current neuro-science research shows our brains learn naturally, that brain-based learning is a learning approach that emphasizes the best natural principles available in the operation of the brain, with the aim of achieving maximum attention, understanding, meaning, and memory. These base learning begins with what is known about the actual structure and use of human thought at various stages of development. Based on the previous explanation, the research conducted by Hazhira Qudsyi (please include the year and write in the bibliography) concludes about learning strategies that can optimize education in early childhood, namely through brain-based learning, because early childhood education (PAUD) is a very basic and strategic education, as the initial foundation for the growth and development of the next child. This research was conducted with qualitative research methods to understand the phenomenon. Based on these results, it was found that optimizing the learning process in early childhood education has its own challenges, especially with the typical characteristics possessed by students, namely early childhood. This article was written with the aim of studying brain-based learning as an effort to optimize early childhood education.